2020
DOI: 10.1080/03050068.2020.1769927
|View full text |Cite
|
Sign up to set email alerts
|

Aligning policy ideas and power: the roots of thecompetitiveness framein European education policy

Abstract: How and why do some ideas attain agenda status while others do not? This paper seeks to explore these questions in the context of the policy changes observed in the evolution of European education policy. By drawing from the literature on agenda-setting and employing process tracing, the paper develops a theoretical argument to investigate the causal mechanisms through which a new problem definition is set. The central argument is that three factors affect the way in which a specific problem definition wins ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
6
0
3
Order By: Relevance
“…Since the 1980s, the EU has considered economic development to be one of the aims of educational policy (Cino-Pagliarello, 2020). However, education and skills development is not one of its competences; this rests with national governments.…”
Section: Developments In Europe 1: the European Qualification Framewo...mentioning
confidence: 99%
“…Since the 1980s, the EU has considered economic development to be one of the aims of educational policy (Cino-Pagliarello, 2020). However, education and skills development is not one of its competences; this rests with national governments.…”
Section: Developments In Europe 1: the European Qualification Framewo...mentioning
confidence: 99%
“…Furthermore, Corbett argued that COMETT, which clearly fell within the remit of the EC, was the gateway to the ERASMUS programme, which was much more likely to be perceived as falling outside the EU’s field of jurisdiction (Corbett, 2009). However, Cino Pagliarello (2017) has shown that despite the initial consensus, a very heated debate that revolved around legal, organizational and financial issues arose with regard to the legitimacy of the COMETT initiative. In the end, the adoption of the initiative meant that in 1986, for the first time, a concrete and far-reaching agreement was reached on greater European cooperation in the field of education.…”
Section: State Of the Researchmentioning
confidence: 99%
“…Until the mid-1980s, the EC’s education policy had been predominantly social and redistributive in character. However, by 1985, an explicit link between education and economic growth had been established in the EC’s strategy to tackle the challenges of technological change, which indicates that its education policy was shifting more towards an economic orientation (Cino Pagliarello, 2017: 89). In the EC’s development of an action programme as a response to technological change, social policy problems took second place behind the main aim of boosting Europe’s economic competitiveness by creating a highly skilled workforce.…”
Section: A Window Of Opportunity For Action By the Ec In The Field Of Education In The 1980smentioning
confidence: 99%
See 2 more Smart Citations